Pemberian Infusa Daun Pepaya (Carica papaya L.) pada Produktivitas Broiler - A K Rylian; N Irwani; Y Sukaryana (PETERPAN (Jurnal Peternakan Terapan), 2021)
One of the efforts to improve broiler productivity is to use natural ingredients, one of which is papaya leaves. Papaya leaves contain substances such as saponins, flavonoids, which can help productivity. The purpose of this study was to analyze the effect of papaya leaf infusion on broiler productivity. Place of research in the Lampung State Polytechnic enclosure. Experimental research by comparing two treatments. The treatment is applied through drinking water at a dose of 25 ml / liter. Consisting of control P0 and treatment P1, each plot contains 50 chickens. The variables observed were ration consumption, body weight gain, ration conversion, it can be concluded from the results of the research that giving papaya leaf infusion (Carica Papaya L.) at a dose of 25 ml / liter in broiler drinking water affected the productivity of broiler